Implementation of the Pancasila Student Profile Strengthening Project in Driving Schools in Alor Regency - Engelbertus Nggalu Bali; Cornelia Theresia Asamal; Vanida Mundiarti (Universitas Nusa Cendana, 2024)
The objective of this research is to observe the transformation of the campus teaching program in strengthening the Pancasila student profile in early childhood education. Using a descriptive qualitative approach, data was collected through observations and interviews with 3 principals and 1 teacher in 4 driving schools. The research results show that P5 activities are adjusted to local culture through enjoyable methods such as mother tongue learning, mangrove planting, and art performances. The projects produced include school gardens, flag ceremonies, and art performances. The learning media used include P5 teaching modules, loose parts media, digital media, and specialized media. The challenges faced include media limitations, unstable electricity and network conditions, and teachers' understanding of modules and assessments. The solutions include workshops, the independent teaching platform, and training in making media